The Remitting Patterns of African Migrants in the OECD - Albert Bollard; David McKenzie; Melanie Morten (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
Recorded remittances to Africa have grown dramatically over the past decade. Yet data limitations still mean relatively little is known about which migrants remit, how much they remit, and how their remitting behavior varies with gender, education, income levels, and duration abroad. We construct the most comprehensive remittance database on immigrants in the OECD currently available, containing microdata on over 12,000 African immigrants. Using this microdata we establish several basic facts about remitting patterns of Africans, and then explore how key characteristics of policy interest relate to remittance behavior. Africans are found to remit twice as much on average as migrants from other developing countries, while those from poorer African countries are more likely to remit than those from richer African countries. We find male migrants remit more than female migrants, particularly among those with a spouse remaining in the home country; that more educated migrants remit more than less educated migrants; and that while the amount remitted increases with income earned, the gradient is quite flat over a large range of income. Finally, we find little evidence that the amount remitted decays with time spent abroad, with reductions in the likelihood in remitting offset by increases in the amount remitted conditional on remitting.
Keywords: O15; F22; J61; 330; Remittances; Migration; Africa